Evaluation of Depression, Anxiety, and Stress in Adolescents and Young Adults with Auditory Neuropathy Spectrum Disorder - Prashanth Prabhu (Scientifica, 2016)
The aim of the present study was to determine the severity of stress, anxiety, and depression using Depression Anxiety Stress Scales (DASS) in adolescents and young adults with auditory neuropathy spectrum disorder (ANSD). DASS was administered to 20 individuals with auditory neuropathy spectrum disorder. The effect of gender on severity of anxiety, stress, and depression on DASS scores was determined. It was attempted to determine the correlation of severity of anxiety, stress, and depression with the reported onset of the problem, degree of hearing loss, and speech identification scores. The results of the study showed that individuals with ANSD had a moderate degree of depression and anxiety. The results also showed that the symptoms were more seen in females than in males. Correlation analysis revealed that DASS scores correlated with the reported onset of condition and speech identification scores (SIS) and the degree of hearing loss showed no correlation. The study concludes that individuals with ANSD experience depression and anxiety and this could be because of the inadequate management options available for individuals with ANSD. Thus, there is a need to develop appropriate management strategies for individuals with ANSD and provide appropriate referral for management of psychological issues.